2011
DOI: 10.13083/reveng.v19i5.335
|View full text |Cite
|
Sign up to set email alerts
|

DESEMPENHO AGRONÔMICO DE CAPIM NAPIER (Pennisetum purpureum) CULTIVADO EM SISTEMAS ALAGADOS CONSTRUÍDOS

Abstract: O objetivo, com a realização deste trabalho, foi estudar o desempenho de Sistemas Alagados Construídos (SACs), cultivados com capim elefante cv. Napier (Pennisetum purpureum), submetidos a diferentes taxas de carregamento orgânico (TCOs), proporcionadas pela aplicação de águas residuárias da indústria de laticínios (ARL), nas condições climáticas de Viçosa - MG. A infraestrutura experimental foi constituída por cinco SACs com fluxo subsuperficial horizontal, constituídos por tanques de 0,40 x 0,75 x 3,00 m, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Constructed wetland systems (CWs) are treatment systems planned and designed to use natural processes involving wetland vegetation, soils, and their associated microbial assemblages to improve water quality [ 1 ]. In CWs—under appropriate environmental conditions—physical, chemical and biochemical processes occur to treat sanitary sewage, industrial effluents and many types of wastewater [ 2 ]. Many countries have adopted these systems [ 3 ] because they require low-cost investments combined with their efficiency and feasibility [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Constructed wetland systems (CWs) are treatment systems planned and designed to use natural processes involving wetland vegetation, soils, and their associated microbial assemblages to improve water quality [ 1 ]. In CWs—under appropriate environmental conditions—physical, chemical and biochemical processes occur to treat sanitary sewage, industrial effluents and many types of wastewater [ 2 ]. Many countries have adopted these systems [ 3 ] because they require low-cost investments combined with their efficiency and feasibility [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the dairy industry, according to Matos et al (2011), a relationship of about 1 to 5 can be observed between volumes of wastewater and milk processed, depending on the final product and the technological level of the industry. The polluting organic load that these effluents present is high, and in the case of inappropriate treatment or disposal, major environmental impacts can be seen in the areas near this type of industry.…”
Section: Introductionmentioning
confidence: 99%